Renal vascular response to angiotensin 1-7 in rats: the role of Mas receptor - Mehdi Nematbakhsh; Azam Mansouri (Wolters Kluwer Medknow Publications, 2018)
Recently a cross talk between angiotensin 1-7 (Ang1-7) receptor (MasR) and angiotensin II receptors types 1 and 2 (AT1R and AT2R) has been highlighted. The effects of MasR antagonist (A779) compared to the vehicle on the renal blood flow (RBF) and renal vascular resistance (RVR) responses to Ang1-7 (300 ng/kg/min) infusion in the absence of Ang II receptors in male and female rats were determined at controlled renal perfusion pressure. Ang1-7 infusion did not alter mean arterial pressure in male and female rats. However, A779 compared to vehicle increased RBF (18% vs 3%) and decreased RVR (13% vs 4%) responses to Ang1-7 infusion significantly (P < 0.05) in male when AngII receptors were blocked. Such observation was not occurred in female animals. Finally it was concluded that renal vascular responses to Ang1-7 administration may not be exerted by MasR in male rats, and these responses are not mediated with AngII receptors.